Prevalence of childhood and adolescent overweight and obesity in Asian countries: a systematic review and meta-analysis - Mazidi, Mohsen (Arch Med Sci, 2018)
INTRODUCTION: We conducted a systematic review and meta-analysis to estimate the prevalence of overweight and obesity in children (aged 5–12 years) and adolescents (aged 12–19 years) in Asian countries. Study design: Systematic review and meta-analysis. MATERIAL AND METHODS: We comprehensively searched specialised databases for relevant studies conducted in Asian countries between January 1, 1999, and May 30, 2017. Random effects models (using the DerSimonian-Laird method) and generic inverse variance methods were used for quantitative data synthesis. Sensitivity analysis was conducted using the ‘leave-one-out’ method. Heterogeneity was quantitatively assessed using the I(2) index. Systematic review registration: CRD42016033061. RESULTS: Among 22,286 identified citations, 41 studies met the inclusion criteria with n = 71,998 and n = 353,513 for children and adolescents. The pooled prevalence (overall, boys and girls) was 5.8% (n = 4175), 7.0% (n = 2631) and 4.8% (n = 1651) for obesity in children aged 5–11 years; 8.6% (n = 30,402), 10.1% (n = 17,990) and 6.2% (n = 10,874) for obesity in adolescents age 12–19 years. For overweight in children the values for overall, boys and girls were 11.2% (n = 7900), 11.7% (n = 4280) and 10.9% (n = 3698) respectively; and for overweight in adolescents, 14.6% (n = 46,886), 15.9% (27,183), and 13.7% (20,574). These findings were robust in sensitivity analyses. In children and adolescents a higher percentage of boys than girls are obese (children = 7.0 vs. 4.8%, adolescents = 10.1 vs. 6.2%, p < 0.001, respectively). Furthermore, in children and adolescents a higher percentage of boys than girls are overweight (children = 11.7 vs. 10.9%, adolescents = 15.9 vs. 13.7%, p < 0.001, respectively). CONCLUSIONS: In view of the number of children who are overweight or obese, the associated detrimental effects on health, and the cost to health-care systems, implementation of programmes to monitor and prevent unhealthy weight gain in children and adolescents is needed throughout Asian countries.